2019
DOI: 10.1016/j.xphs.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Hinge Flexibility on the Solution Structure of Antibodies at Concentrated Conditions

Abstract: Employing two different coarse-grained models, we evaluated the effect of intramolecular domaindomain distances and hinge flexibility on the general solution structure of antibodies (mAbs), within the context of protein-protein steric repulsion. These models explicitly account for the hinge region, and represent antibodies at either domain or subdomain levels (i.e., 4-bead and 7bead representations, respectively). Additionally, different levels of mAb flexibility are also considered. When evaluating mAbs as ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Recently, introducing domain flexibility, in particular torsion at the hinge, was found to have a significant effect on S(q) over a large q range by increasing packing and osmotic compressibility. 53 At high concentrations, hinge flexibility would allow the molecule to adopt more configurations, increasing the probability of encountering favorable short-range attractions. This hinge effect will have a larger influence as protein concentration increases.…”
Section: Modeling Ppi Across Protein Concentrationmentioning
confidence: 99%
“…Recently, introducing domain flexibility, in particular torsion at the hinge, was found to have a significant effect on S(q) over a large q range by increasing packing and osmotic compressibility. 53 At high concentrations, hinge flexibility would allow the molecule to adopt more configurations, increasing the probability of encountering favorable short-range attractions. This hinge effect will have a larger influence as protein concentration increases.…”
Section: Modeling Ppi Across Protein Concentrationmentioning
confidence: 99%
“…Hinge flexibility, on the other hand, still plays an important role in facilitating quaternary structural rearrangement to achieve a more compact but stable solution structure at very high mAb concentrations. 16 Recently, Vlachy and collaborators 178 arrived at similar conclusions by extending Wertheim’s theory for a 7-CG-site mAb model. These authors found that the critical temperature and concentration are sensitive to the imbalance of the interactions involving the C H 3 and variable fragment (F V ), but they are marginally affected by the actual strength of the intermolecular interactions.…”
Section: High-concentration Physical Instabilitiesmentioning
confidence: 68%
“… Representation of the hierarchy of computational protein models based on their level of resolution, using an IgG2 mAb (PDB: 1IGT) as an example. These types of models include: atomistic; high-resolution coarse-grain (based on the model from Bereau and Deserno 13 ); low resolution coarse-grain from Blanco et al; 14 simplified coarse-grain using the 12-bead model from Calero-Rubio et al 15 and the 4- and 7-bead models from Blanco et al; 16 and a continuum model based on Wertheim’s theory adapted by Skar-Gislinge et al 17 The arrow indicates the direction in which the resolution-level increases for each model. …”
Section: Types Of Protein Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Far-field interactions that modulate the molecular distance distribution in solution, as well as short-range weak interactions that lead to transient complexes, may cause phase separation, promote the formation of immunogenic irreversible aggregates, or cause excessive solution viscosity. [1][2][3][4][5][6][7][8] In the search for conditions of pH, ionic strength, and excipients that yield safe and efficacious formulations, powerful biophysical methods have been used by different laboratories to predict and characterize higher-order structures and interactions of protein pharmaceuticals, including computational approaches, 5,[9][10][11] and experimental techniques such as static and dynamic light scattering, small-angle scattering, analytical ultracentrifugation, and chromatography. [12][13][14][15][16][17][18][19][20][21] However, a key experimental difficulty for the characterization of weak protein interactions with any technique is the need to study concentrated solutions that are thermodynamically and hydrodynamically nonideal.…”
Section: Introductionmentioning
confidence: 99%